Cross-Cultural Experience: Pengenalan Busana Trandisional Bali kepada Mahasiswa Thailand di Walailak University - Putu Lady Nova Kristina; Luh Made Dwi Wedayanthi (Lembaga Pengembangan Kinerja Dosen, 2025)
Cross-Cultural Experience: Introducing Balinese Traditional Clothes to Walailak University Students in Thailand is part of an international community service program (KKN) that students from the Institute of Technology and Education Markandeya Bali took part in. The main goal of this activity was to introduce Balinese cultural values by teaching students about traditional Balinese clothes as a way to learn about different cultures. This study uses a qualitative descriptive approach with the CIPP (Context, Input, Process, Product) evaluation model to evaluate the success of the activity. The results of this activity show that there is an increase in understanding, fostering an attitude of appreciation, and strengthening cross-cultural communication among students. This activity is effective as a medium for cultural diplomacy and experiential learning.